Relevansi Teori Perkembangan Piaget dan Erikson dalam Pembentukan Karakter dan Kognisi Anak di Era Digital - Herliyana, Bella; Maslahah, Thobiatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
The cognitive and character development of children in the digital age is becoming an increasingly important topic as information technology advances rapidly. Jean Piaget and Erik Erikson's developmental theories offer relevant frameworks of understanding to analyze how children adapt to the digital environment. This study aims to analyze the influence of digital technology on cognitive development based on Jean Piaget's theory and character development according to Erik Erikson's psychosocial theory. The method used is descriptive qualitative through literature analysis. The results show that digital technology can accelerate the cognitive learning process, but risks reducing physical exploration. In addition, digital platforms support social identity formation, although they present challenges in managing self-identity. This research is expected to serve as a basis for designing strategies to support optimal child development in the digital era. By understanding the interaction between classical developmental theories and the digital world, it is hoped that more effective ways can be found to support children's development in the present.